Legal and Medical Education Compared: Is It Time for a Flexner Report on Legal Education? - Robert M. Hardaway (Washington University Law Quarterly, 1981)
The purpose of this Article is to explore the common elements of legal and medical education and to compare the reform movements in each profession, with a view toward finding an explanation for the widely differing conditions that exist today in the education of each profession.
Keywords: Graduate medical education; Legal education; Professional education; United States; Abraham Flexner